The Issue of the Concept of Law Enforcement Technique in the Context of Legal Technique Theory - Kocharyan, Sergey (Bulletin of Yerevan University C: Jurisprudence, 2024)
The issues of classification legal techniques into types andsubtypes are studied in the article, where different hypotheses of the mentioned phenomenon arepresented and the necessity of the existence of legal technique as an independent type of legaltechnique is substantiated.Regarding the concept of legal technique, there are certain disagreements in the views of scholars.Some of them understand the legal technique only as a rule-making technique. Authors opposedto this approach define legal technique broadly as a set of rules, tricks, ways of preparing,compiling, formulating, coordinating and accounting legal documents in general.Based on the listed points of view, the article grouped them according to the breadth of contentand activity coverage, and they were called broad and narrow approaches. Proponents of a narrowapproach extend this concept only to the field of law-making and identify legal and law-makingtechniques.Of the various approaches to the concept of legal technique, the broad and general understanding,which includes other areas of legal activity, including law enforcement, was considered the mostacceptable. The issue in question led to the separation of existing types of legal techniques, theirclassification, division into two-type and multi-type groups, which made it possible to justify the"right to exist" of legal technique as a separate type of legal technique.
Keywords: legal technique; legal framework regulation; legal technology; law enforcement technique; classification; typology; legal activity